Direct immunofluorescence testing in vasculitis—A single institution experience with Henoch‐Schönlein purpura. (8th November 2017) - Feasel, Patrick; Billings, Steven D.; Bergfeld, Wilma F.; Piliang, Melissa P.; Fernandez, Anthony P.; Ko, Jennifer S.
Abstract : Background: Direct immunofluorescence (DIF) panels (IgG, IgA, IgM, C3 and fibrinogen) are ordered for clinically suspected vasculitis, with frequently negative results. Methods: Cases submitted for DIF and histology (2010‐2014) with "vasculitis" in the clinical data were examined, and the electronic medical record reviewed for clinical suspicion of Henoch‐Schönlein purpura (HSP). Peri/intravascular IgA was considered positive, other reactants non‐specific and no immunoreactivity negative. Results: Vasculitis was the given indication for 20% (258/1318) of DIF studies. HSP was clinically suspected in 36% (95/258). In this setting, leukocytoclastic vasculitis (LCV) was common (66%, 63/95) and DIF was positive in 43% (27/63). One hundred percentage of DIF+ had LCV+. In cases without HSP suspicion, 26% (42/163) were LCV+ and <1% DIF+. Of the 258 cases, LCV+ greatly enriched for DIF+ (105/258 LCV+ with 28/105 [27%] DIF+), captured 100% of HSP and included cases with non‐specific DIF/etiologic findings. In LCV cases, DIF positivity was not seen, HSP was not diagnosed and non‐specific DIF findings were common. Conclusions: LCV is an H&E‐based histopathologic diagnosis that can have positive, negative and non‐specific DIF results that are rarely contributory except in the setting of HSP, where DIF is best utilized with IgA as the sole immunoreactant. H&E‐based triage of DIF orders is recommended.